Flor de Mangueira: a reinvenção da velhice num grupo de mulheres - Luiz Divino Maia (2013)
This dissertation is an ethnographic description of the interactive meetings with a group called "Flor de Mangueira", composed of old women looking for a brief escape from the conventional roles imposed by family. The group moments they fell better and with more value than they are in the homes - and totally free to behavior in other different way. In group, they can play other social roles. The work can also be seen as an ethnographic invention. With reasonable freedom, several experiments were performed to analyze the social phenomena. In this case, the anthropologist assumed the role of the inventor of a reality to achieve the understanding of an experience essentially "real" and prevailing for the women in that group.